2019
DOI: 10.1007/s12559-019-09638-y
|View full text |Cite
|
Sign up to set email alerts
|

PAS3-HSID: a Dynamic Bio-Inspired Approach for Real-Time Hot Spot Identification in Data Streams

Abstract: Hot spot identification is a very relevant problem in a wide variety of areas such as health care, energy or transportation. A hot spot is defined as a region of high likelihood of occurrence of a particular event. To identify hot spots, location data for those events is required, which is typically collected by telematics devices. These sensors are constantly gathering information, generating very large volumes of data. Current state-of-the-art solutions are capable of identifying hot spots from big static ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The shortcomings of these methods lie in the fact that they may produce invalid results, require historical data or a predefined number of hot spots, and are not suitable for big data processing. Detailed reviews of the existing methods for HSID can be found in [5], [8]. The literature on employing concepts of fuzzy logic for HSID is limited.…”
Section: B Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The shortcomings of these methods lie in the fact that they may produce invalid results, require historical data or a predefined number of hot spots, and are not suitable for big data processing. Detailed reviews of the existing methods for HSID can be found in [5], [8]. The literature on employing concepts of fuzzy logic for HSID is limited.…”
Section: B Related Workmentioning
confidence: 99%
“…In this subsection we provide a high-level description of the streaming SeleSup-HSID algorithm, based on the earlier works on SeleSup-HSID in [5] and [6], and used here as the method into which we introduce fuzzy concepts. A full description can be found in [8] and our implementation is available on GitHub 1 (using Apache Spark Streaming [14]). The method is designed to work on a large data stream of incident data, processed as a sequential chain of microbatches containing incidents from a given time interval.…”
Section: Overview Of Streaming Selesup Hsidmentioning
confidence: 99%
See 3 more Smart Citations